Factors Influencing Tax Avoidance and Tax Evasion in Nigeria: A Case Study of Wukari, Taraba State - Bako, Paul Matudi (Universitas Syiah Kuala, 2021)
Objective The goal of this study is to assess several factors that influence tax avoidance and evasion in Nigeria, with a focus on Wukari, Taraba State. Particularly this study is aimed to ascertain the influence of corruption on individual tax avoidance and evasion in Nigeria, whether lack of transparency and accountability in public institutions influences individual tax avoidance and evasion in Nigeria, to examine the influence of tax system injustice on individual tax avoidance and evasion in Nigeria, and to evaluate the impact of tax system complexity on individual tax avoidance and evasion in Nigeria.Design/methodology This study adopts a survey research design with a sample size of 308 questionnaires administered and 230 questionnaires were collected which represents 75% response rate. Descriptive statistics like mean, standard deviation and percentages, inferential statistics like multiple regressions were used.Results It was found that corruption, lack of transparency and accountability, tax system injustice and tax system complexity all have a substantial impact on tax avoidance and evasion in Nigeria. Urgent step should be taken by public office holders in particular and government representatives in general to live above board when it comes to transparency and accountability. In addition, there should be zero tolerance for corruption within and outside the tax system; anyone found guilty of corruption should be made to face the wrath of the law. Conclusively, Nigeria government should make deliberate efforts to ensure the nations financial statement is published depicting our revenue as well as expenditure incurred regularly (monthly basis, quarterly or annually).Limitation/Suggestion This study concentrated on only four factors identified to have an influence on tax avoidance and evasion in Nigeria. It is also constrained to Wukari, Taraba State which is just one amongst the sixteen local governments in the State and as such may not be applicable to other local governments within and outside the State.